PENGARUH AKUNTABILITAS, TRANSPARANSI, DAN PENGAWASAN TERHADAP KINERJA ANGGARAN DENGAN KONSEP VALUE FOR MONEY PADA ORGANISASI PERANGKAT DAERAH KABUPATEN GROBOGAN - Reza Cahya Eka Suci; Abdul Rohman (Diponegoro Journal of Accounting, 2023)
This study aims to test and analyze the effect of accountability, transparency, and supervision on budget performance with the concept of value for money in Regional Apparatus Organizations (OPD) in Grobogan Regency. The variables used in the test are accountability, transparency, and supervision as independent variables, and budget performance with the concept of value for money as the dependent variable. The variables used in the test are accountability, transparency, and supervision as independent variables, and budget performance with the concept of value for money as the dependent variable. This study used a questionnaire distribution to respondents who were used as representatives of each OPD in Grobogan Regency with a total sample of 48 samples. The method used in this sampling is a census. The analytical method used in this research is multiple linear regression analysis method. The results showed that simultaneously and partially the accountability, transparency, and supervision variables showed positive and significant results on budget performance with the concept of value for money at OPD in Grobogan Regency.